The influence work effort, idealism, and audit expertise towards audit judgment performance - Tjiptohadi Sawarjuwono, Dhita Alifya Fitri, (Opción, 2020)
The case of failed audits experienced by a number of large companies caused auditors to lose the trust of public. Therefore, the effort that can be done by the auditors is to improve the quality of audit judgment. This study aims to examine the influence of work effort, idealism and audit skill on audit performance evaluation. Quantitative research method was applied with three variables to be tested, namely work effort, idealism, and audit expertise. The results of this study indicate that work effort and audit expertise affects audit performance judgment, while idealism does not affect audit performance evaluation.